(untitled) (Research, Society and Development, 2021)
The bovine production on pastures is a sustainable activity, responsible to generating income and employments in many tropical regions. However, in this system a major obstacle occurs during long dry periods, when the forages show low nutritional quality. In this research we evaluated the in vitro digestibility and degradability of Urochloa decumbens and Cynodon dactylons var Tiffton 85 inoculated with isolates of Aspergillus spp. from the gastrointestinal tract cattle. Four cows with rumen fistula were used as rumen contents donors to determine the in vitro digestibility of dry matter (IVDMD). The treatments were, as follows: control - No fungal inoculum, AT13 – (with Aspergillus terreus isolate), AF69 – (with Asperillus fumigates isolate, MIX (with mix of fungi AT13 and AF69). The analyses were performed in rumen simulator with four replications. The gas production was determined by semi-automatic method for both gas and the mechanics ability to fiber colonization of these fungi isolates were evaluated by scanning electron microscopy. The inclusion of AF69 and MIX promoted significant increase of IVDMD of U. decumbens (41.4 - 42.1%). The dry matter degradability were not influenced by the inoculums types using the by semi-automatic gas production method However, they linearly increased with fermentation time. The two isolates of Aspergillus spp. were able to colonize the U. decumbens fiber showing production of mycelium and reproductive structures in electronic microscopic analyses. The addition these Aspergillus isolates promotes significant increase of IVDMD to U. decumbens, indicating promising potential for development of microbial or probiotic additive to cattle raised on lignified tropical pasture.